Clinical and morphological features in patients with advanced endometrial cancer treated with immunotargeting therapy - L. A. Kolomiets; M. N. Stakheeva; O. N. Churuksaeva; A. B. Villert; A. L. Chernyshova; V. G. Sisakyan; I. Yu. Lots; N. M. Chernorubashkina; V. N. Zhurman; A. A. Grechkina; E. N. Aleksandrova; N. E. Musaeva; et al. (ABV-press, 2023)
Background. Endometrial cancer (EC) is one of the most significant oncogynecological problems. The main mortality cause in this disease, as in the case of other malignant neoplasms, is the tumor progression. The presence of mutations associated with mismatch repair-deficient is of great prognostic importance. Immunotargeting therapy (ITT), lenvatinib in combination with pembrolizumab, seems to be the most effective solution in the second line treatment of advanced EC without microsatellite instability. At the same time, the group of such patients is heterogeneous in terms of progression-free survival (PFS) on ITT. So that it determines the continuing need to search for reliable parameters steadily associated with the PFS duration in this type of treatment.Aim. To analyze the clinical and morphological features in patients with advanced EC depending on the PFS duration on ITT. Materials and methods. The study included data on patients (n = 36) with advanced EC who received ITT in oncological dispensaries in Siberia and the Russian Far East. The overall patients' group was analyzed using the Kaplan-Meier method. PFS was defined as the time from the ITT initiation until progression or death against the background of treatment. The influence of the selected factors (clinical and morphological parameters, treatment features, and adverse events) on PFS was assessed using a log-rank criterion. The study participants were then divided into 2 subgroups (15 women and 9 women) according to median PFS. Mann-Whitney tests for independent samples (quantitative measures), and Fisher's tests (qualitative measures) were used to identify significant differences in comparison subgroups for the selected factors. Differences were considered statistically significant when the significance level was reached (p <0.05); data at the statistical trend level (p <0.10) were also discussed.Results. In the study group, median PFS on ITT was 9.7 months (cut-off point), which was accepted as a response criterion. Among the 74 parameters reflecting clinical and morphological features in patients with advanced EC, metastatic lesions of pelvic lymph nodes (p = 0.028), para-aortic lymph nodes (p = 0.014), bone metastases (p = 0.080), and degree of estrogen receptor expression in tumor cells (p = 0.071) were associated with PFS. Partial regression as the maximal response to ITT (62.5 % vs 7.14 %, p = 0.011), as well as longer duration of response (median PFS 15.11 ± 1.10 months vs 4.47 ± 0.57 months, p = 0.00007), and the absence of foci in the pelvic/para-aortic lymph nodes (89 % vs 50 %, p = 0.069, and 89 % vs 47 %, p = 0.048, respectively), were more frequently observed in patients with a duration of median PFS ≥9.7 months compared to those with progression before 9.7 months. Stabilization as the maximum response to ITT (78.6 % vs 37.5 %, p = 0.072) was more frequently registered in the subgroup of patients with progression up to 9.7 months.Conclusion. ITT can be considered as a potentially promising therapeutic option in advanced EC. Further research in this direction should be aimed at finding criteria to identify patients with EC who would have most benefit from this type of therapy more accurately.